-4(2u-6)=-4-12u

Simple and best practice solution for -4(2u-6)=-4-12u equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(2u-6)=-4-12u equation:


Simplifying
-4(2u + -6) = -4 + -12u

Reorder the terms:
-4(-6 + 2u) = -4 + -12u
(-6 * -4 + 2u * -4) = -4 + -12u
(24 + -8u) = -4 + -12u

Solving
24 + -8u = -4 + -12u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '12u' to each side of the equation.
24 + -8u + 12u = -4 + -12u + 12u

Combine like terms: -8u + 12u = 4u
24 + 4u = -4 + -12u + 12u

Combine like terms: -12u + 12u = 0
24 + 4u = -4 + 0
24 + 4u = -4

Add '-24' to each side of the equation.
24 + -24 + 4u = -4 + -24

Combine like terms: 24 + -24 = 0
0 + 4u = -4 + -24
4u = -4 + -24

Combine like terms: -4 + -24 = -28
4u = -28

Divide each side by '4'.
u = -7

Simplifying
u = -7

See similar equations:

| (6/5x)-(5/8)=(3/4x) | | -12-8(x-3)=-6(x-1) | | 6x-11x-12=-3(x-2) | | -(1+8X)=6-9X | | -9(10x+11)=351 | | 4-2y-y=2 | | tanx=(3/2)^(1/3) | | d=7+5x-8x | | 2x=1.8 | | 6-5x=9x-10x-6 | | 3x+7=8x-63 | | -12=-7–7/2s | | 14+7K=9K-2 | | -8(10x+3)=376 | | f(x)=4x^2-24x+31 | | 19v=-114 | | 3+4(x+6)=11 | | -9=2/3x–17 | | 8-4x=4-3(2x-6) | | 5(8v-8)=-6 | | 2x+3=-55 | | Y=1/2X-18 | | 65=5(5x-17) | | -2(x-3)=5(2x+13) | | 14+A=2-2A | | 2/3x–17=-9 | | -q=-52 | | f(x)=6xsquar | | (15)65=5(5x-17) | | 1-r=9 | | ln(x-3)=ln(1/x) | | 9xy-4+xy+8= |

Equations solver categories